2022
DOI: 10.36534/erlj.2021.02.08
|View full text |Cite
|
Sign up to set email alerts
|

Greek preschool teacher’s views about language activities in early childhood education during Covid‑19. A chance for change?

Abstract: The aim of this research is to investigate the views of preschool teachers about their "readiness" for elearning, the barriers they had faced while using it in early childhood education, the teaching practices during distance learning of language, and the transformations that had to be done in these, their effectiveness, and finally the utilization of the digital tools in the teaching of language after their return to the real classes. Views from ten Greek preschool teachers were collected with semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…In addition, the absence of pedagogical material related to mathematical concepts in face-toface schooling led them to create and/or recreate digital material. Previous studies found similar findings [4,8,9].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In addition, the absence of pedagogical material related to mathematical concepts in face-toface schooling led them to create and/or recreate digital material. Previous studies found similar findings [4,8,9].…”
Section: Discussionsupporting
confidence: 81%
“…Even though preschool teachers reported that during distance learning, they used digital tools for interdisciplinary activities [4], after returning to face-to-face schooling, they avoided using them. However, some teachers accept that this experience supplied them with technological skills that could be utilized in similar situations [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations